Simulation of creep deformation in the foundation of Tar Island Dyke - Morsy, Mohammed M.; Morgenstern, N.R.; Chan, D.H. (Canadian Geotechnical Journal, 1995)
Tar Island Dyke is a 92 m tailing dyke for retaining oil sand tailings and has been operated by Suncor in Fort McMurray, Alberta. Construction of the dyke began in the mid-1960's adjacent to the Athabasca river. The foundation of the dyke consists of a layer of interbedded silts and clay overlying a basal sand stratum. Stresses imposed by the dyke on the foundation clay have been causing continuing movement of the structure over 30 years. Movements of the dyke have been monitored for over 25 years and show significant creep deformation of over 1 m in the foundation clay. Pore pressure in the clay was monitored, with little pore pressure change during this period. Therefore the movement was mostly due to creep rather than consolidation. The unique feature of this case is that the loading due to the dyke has been essentially constant for over 15 years but movement has continued. An effective stress model for creep is adopted to simulate the construction of the Tar Island Dyke. The model is based on critical state soil mechanics and uses secondary consolidation and the Taylor Singh-Mitchell creep relationships. The model is able to capture the movement of the dyke and its foundation, and good agreement is obtained between the calculated and measured deformations. A sensitivity study has been carried out to study the effect of varying the creep parameters on the results of the analysis. Key words : Tar Island Dyke, creep mechanism, finite element, clay foundation, effective stress model, pore-water pressure.